Association between stress and information security policy non-compliance behavior: A meta-analysis. Issue 124 (January 2023) - Aggarwal, Akshay; Dhurkari, Ram Kumar
Highlights: Meta-analysis conducted to examine the association between stress and ISP compliance. A weak positive association exists between stress and ISP non-compliance behavior. The heterogeneity test validates the results of the meta-analysis. Few of the demographic characteristics are significant predictors of this association. Abstract: Stress plays a critical role in information security policy (ISP) compliance behavior. Since there are multiple sources of stress, the current literature does not provide a consistent view of the association between stress and ISP compliance behavior. Understanding the significance of the association between stress and ISP compliance behavior is valuable for managers, especially in managing the tradeoff between stress and ISP compliance behavior among individuals. It is also important to understand why there has been so much inconsistency in past studies. Thus, we attempted a meta-analysis to provide a generalized interpretation of the association between stress and ISP non-compliance behavior. A systematic literature review and a meta-analysis are conducted to examine the underlying contradiction and aggregate the findings of relevant studies. The results of this meta-analysis confirmed a weak positive correlation between stress and ISP non-compliance behavior. Demographic characteristics like age, country, and the category of the respondents (employee vs non-employee) are significant predictors of the association between stress and ISP non-compliance behavior. The meta-analysis presented here is also pertinent to the recent COVID-19 pandemic, which forced organizations to engage with their employees in new working conditions, putting employees under more stress and strain.